Variables Affecting the Retention Intentions of Students in Higher Education Institutions: A Comparison Between International and Domestic Students - Haverila, Matti; Haverila, Kai; McLaughlin, Caitlin (Journal of International Students, 2020)
The purpose of this study was to investigate the differences between domestic and international students with regards to the variables affecting students’ retention intentions. Altogether, 15 variables related to retention intentions were examined and significant differences were found in six of these variables. Variables related to personal issues (e.g., medical or family difficulties) were of equal importance to both groups, while the importance of institution and performance-centric variables differed between the groups. Social integration, ineffective study skills, difficulty adjusting to college life, poor extracurricular activities, and poor housing arrangements were perceived to be significantly more important by international students, while poor quality of instruction was perceived to be significantly more important by domestic students. Thus, international and domestic students require different retention strategies on the part of the institution.